THE PROBLEM OF THE TRANSITION FROM THE PERMIAN TO THE TRIASSIC SERIES IN SOUTHEASTERN FRANCE: COMPARISON WITH OTHER PERITETHYAN REGIONS - Durand M. (My University, 2006)
In the French sedimentary basins, widespread alluvial deposits sealing narrow Permian troughs are referred to as 'Buntsandstein'. An Early Triassic age is generally put forward despite a lack of any Scythian biochronological elements. In Provence (Southeast Basin) some doubts remain about the age of the latest Permian deposits, and the oldest Triassic fossils (Anisian palynomorphs) appear in the upper 'Buntsandstein'. Three types of contact occur: disconformity overlain by a quartz-conglomerate, apparent transition, and angular unconformity, according to an increasing basal incompleteness of the 'Buntsandstein'. Whereas the conglomerate was deposited under arid conditions, the overlying fluvial deposits indicate a marked climate change. A transect from France up to the Germanic Basin centre shows that the 'French Buntsandstein' cycle might begin considerably before the end of the Permian; the Early Triassic arid 'event' is Dienerian/Smithian in age; and the Provenqal 'basal' conglomerate corresponds to the uppermost part of a coeval subordinate cycle, and thus the underlying sub-Triassic unconformity represents a hiatus estimated at 10-15 Ma. Works in progress confirm that sedimentary climate indicators constitute powerful tools for correlations within non-marine formations devoid of biostratigraphical marker that straddle the Permian Triassic boundary, at least on the scale of the Western European Plate. © The Geological Society of London.
Keywords: Permian; Anisian; Paleozoic::Permian; Палеозой::Пермская; Mesozoic::Triassic::Middle::Anisian; Мезозой::Триасовая::Средний::Анизийский